My Website Reads at an Eighth Grade Level: Why Plain Language Benefits Your Users (and You). Issue 1 (2nd January 2017) - Skaggs, Danielle
ABSTRACT: Writing in plain language aims to help users find what they need and ensures that the information is both useful and understandable. This is key for distance students whose primary library interaction may be with the library Website. A mix of user research and readability scores can be used to measure whether content is findable, useful, and understandable. There are several strategies authors can adopt to help them write in plain language, including keeping the users' needs and tasks in mind and structuring the content so that it can be quickly scanned. Converting existing Website content to a plain language format can be a large task; running a content audit can help determine which pages should be prioritized for revision. Once the Website is written in plain language, an ongoing content strategy is necessary to help it stay that way.